Review of the West Indian species of Efferia Coquillett (Diptera: Asilidae) with 13 new species and checklist: Part II. Hispaniola, Puerto Rico, and Lesser Antilles including Tobago and Trinidad - Scarbrough, Aubrey G.; Perez-Gelabert, Daniel E. (Zootaxa, 2009)
The species of Efferia from Hispaniola, Puerto Rico, and the Lesser Antilles are reviewed. Twenty species are recognized including 12 new species from the Dominican Republic: E. alia sp. nov., E. angusta sp. nov., E. bullata sp. nov., E. clava sp. nov., E. exacta sp. nov., E. incisura sp. nov., E. picea sp. nov., E. serrula sp. nov., E. sinuosa sp. nov., E. suspiciosa sp. nov., E. spinula sp. nov., and E. woodleyi sp. nov., and 1 from Puerto Rico: E. montensis sp. nov. Seven previously described West Indian species are recognized: E. forbesi (Curran, 1931), E. fortis (Walker, 1855), E. fulvibarbis (Macquart, 1848), E. haitensis (Macquart, 1848), E. nigrimystacea (Macquart, 1847), E. portoricensis (Curran, 1919), and E. stylata (Fabricius, 1775). An unresolved species from Tobago and Trinidad is also reported. All of these belong to the aestuans species group. New synonyms include: E. pachychaetus (Bromley, 1928) = E. fulvibarbis (Macquart, 1848), syn. nov.; E. tortola (Curran, 1928) = E. stylata (Fabricius, 1775), syn. nov.; and Phoneus flavotibius Bigot, 1878, = E. fortis (Walker, 1855), syn. nov. Efferia haitensis (Macquart, 1848) is removed from synonymy with E. stylata (Fabricius, 1775). The male of E. stylata is discovered and described. Lectotypes are designated for E. haitensis and E. nigrimystacea. The species is removed from the list of species from Hispaniola. Endemism is high with most species limited to single islands. Only E. stylata and E. forbesi occurring in Puerto Rico and the Virgin Islands and E. nigrimystacea in the Lesser Antilles are more widespread. Hispaniola has the greatest diversity with 15 species whereas Puerto Rico, the British and US Virgin Islands, and the Lesser Antilles have 5. Keys, illustrations of the left wing of selected males, and terminalia of all known species are included. A check-list of the West Indian species of Efferia, including an unresolved species from Tobago and Trinidad, is also provided.